PENGARUH SOCIAL MEDIA INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN SURVEY TERHADAP KONSUMEN ROYAL ORCHID RESTO - I Wayan Agus Juliana; Ni Ketut Murdani, S.Sos, SE, MM; Ni Luh Indiani., SE., MM (Jurnal Actual Organization Of Economic, 2023)
Restaurant is a physical component of tourism, which functions as one of the supporting tourism facilities for services, so that tourists who come to Badung Regency can easily find the various types of restaurants they want. One of the tourist destinations in Badung Regency which is always crowded with domestic tourists. This study aims to determine the influence of Instagram social media on purchasing decisions. The population uses Royal Orchind Resto consumers and a sample of 95 respondents. Methods of data collection using a questionnaire. Data analysis techniques used validity test, reliability test, classic assumption test, simple linear regression analysis, coefficient of determination test, and t test. From the results of the study, the results obtained were Instagram social media having a positive and significant effect on purchasing decisions, where a t-count value of 11.191 was obtained and a sig value of 0.000. The influence of Instagram social media on purchasing decisions is 57.4%. The advice that can be given by researchers is that Royal Orchid Resto should create more interesting content and work with celebrities to become brand ambassadors in promoting at Royal Orchid Resto, so that later there will be more likes from Instagram media users and make a price policy that is in accordance with the quality offered.